Collaborative Governance in Overcoming Stunting in Bantaeng Regency - Rahayu, Sri; Mahsyar, Abdul; Fatmawati (GoAcademica Research & Publishing, 2024)
Stunting is included in one of the SDGs agenda, which must be addressed immediately because it affects future human resources quality. This study aims to analyze the collaboration carried out by the Government of Bantaeng Regency in accelerating the reduction in the stunting prevalence rate. The research method used is qualitative with a case study type. Observation, interviews, documentation, and media reviews carried out data collection techniques. The data analysis techniques are data reduction, data presentation, and concluding. The data obtained were analyzed using Nvivo 12 plus software. The study results show that the principled form of involvement in stunting prevention collaboration in Bantaeng Regency is carried out by forming a discussion room to identify problems so that stakeholders have a good understanding of stunting and there is no individual interest in the collaboration that is carried out. The obstacles experienced in tackling stunting in Bantaeng Regency are that it needs to be more transparent and resources are still limited, so the role of the private sector and academics is needed.